Kinetic Theory of Nonequilibrium Ensembles, Irreversible Thermodynamics, and Generalized Hydrodynamics Volume 2. Relativistic Theories - Eu, Byung Chan (Springer International Publishing : Imprint: Springer, 2016)
This book presents the fundamentals of irreversible thermodynamics for nonlinear transport processes in gases and liquids, as well as for generalized hydrodynamics extending the classical hydrodynamics of Navier, Stokes, Fourier, and Fick. Together with its companion volume on nonrelativistic contexts, it provides a comprehensive picture of the relativistic covariant kinetic theory of gases and relativistic hydrodynamics of gases.Relativistic theories of macroscopic irreversible processes must strictly conform to the thermodynamic laws at every step and in all approximations that enter their derivation from the mechanical principles. Upholding this as the inviolable tenet, the author develops theories of irreversible transport processes in fluids (gases or liquids). They apply regardless of whether the processes are near to or far removed from equilibrium, or whether they are linear or nonlinear with respect to macroscopic fluxes or thermodynamic forces. The irreversible covariant Boltzmann as well as the covariant form of the Boltzmann-Nordheim-Uehling-Uhlenbeck equation is used for deriving theories of irreversible transport equations and generalized hydrodynamic equations for either classical gases or quantum gases. They all conform rigorously to the tenet. All macroscopic observables described by the so-formulated theories therefore are likewise expected to strictly obey the tenet.